- Thread starter
- #1

- Thread starter Jonter
- Start date

- Thread starter
- #1

- Admin
- #2

\(\displaystyle \d{u}{x}-\frac{B}{m}u=\frac{A}{m}u^{-1}\)

We see we have a Bernoulli equation. Multiply by \(u\):

\(\displaystyle u\d{u}{x}-\frac{B}{m}u^2=\frac{A}{m}\)

Let \(v=u^2\) hence \(\displaystyle \d{v}{x}=2u\d{u}{x}\) and so we have:

\(\displaystyle \d{v}{x}-\frac{B}{2m}v=\frac{A}{2m}\)

We now have a linear equation, and so can you proceed?

Note: I have moved this thread to our "Differential Equations" forum.

- Jan 29, 2012

- 1,151